Peran kepercayaan merek sebagai variabel mediasi pada hubungan kepribadian merek halal dan loyalitas merek - Mirza Putri Andita; Sulastri Sulastri; Zakaria Wahab (Jurnal Manajemen Maranatha, 2021)
Customer loyalty is currently becoming one of the crucial things for the company to survive in competitive markets. Globalization causes imported cosmetic products from global brands can enter other countries’ markets easily. Nowadays imported cosmetic brands from other countries such as USA, South Korea, and Japan come and take a huge of Indonesia’s skincare market share. This change becomes threat for local cosmetics brands in Indonesia such as Wardah. This study was conducted to analyzes whether halal brand personality affects brand loyalty. This study also analyzes whether brand trust can mediate the relationship between halal brand personality and brand loyalty. The sampling method used in the study is non-probability sampling with snowball technique. The data in this research were obtained by distributing an online questionnaire to 111 respondents who were Wardah’s face skincare consumers and had shopped at least twice in the last 1 year (January 2020-July 2021). The data of this study were analyzed using Structural Equation Modeling method with SmartPlS 3 software. The results of this study indicate that halal brand personality has positive and significant effect on brand loyalty, brand trust has positive and significant effect on brand loyalty, and brand trust successfully mediates the relationship between halal brand personality and brand loyalty. This study provides new insight which suggests marketers develop branding strategies in order to strengthen brand trust which leads to maintaining customer loyalty.